TEACHING AND DEVELOPING ENGLISH TO MULTILEVEL STUDENTS THROUGH PROFESSIONAL VOCABULARY - Ominakhon Shukurdinovna (Scholar Express Journal, 2023)
Teaching a foreign language to students with different levels of knowledge with the help of specialized subjects, their development through sectoral lexical exercises is a means of ensuring that they acquire future professional communicative competence. The introduction of multi-level authentic and sectoral texts based on a step-by-step plan will not only affect their English learning, but also their fields with the help of English and increase their knowledge. In this article, we will discuss the difficulties that ITCI (Information Technology and Computer Ingineering ) students of different levels of education face in increasing their vocabulary in English and ways to overcome them
Keywords: cognitive thinking; vocabulary; assimilation